Case study: software solution for vehicle license plate detection; Известия Томского политехнического университета [Известия ТПУ]. Промышленная кибернетика; Т. 2, № 1 - Levin S. M. Semyon Mikhailovich (2024, 2024)
This article illustrates the development of a software product aimed at automated recognition and classification of vehicle license plates using camera video images. The project goal is to facilitate and optimize the processes of access control and traffic management in restricted areas, including parking lots and private and corporate zones. The developed software product enables real-time analysis of the video stream, extraction of license plates, and their subsequent reading and identifi-cation. The article describes the technological development, including the selection of software tools. Furthermore, it discuss-es the advantages of the created software compared to other available market solutions, highlighting its efficiency, flexibility in settings, and potential for scaling and integration with other security and access management systems